Muscle contributions to medial and lateral tibiofemoral compressive loads during sidestep cutting - Bryant, A. L.; Sritharan, P.; Schache, A. G.; Opara, D. A. (Journal of Biomechanics, 2020)
The tibiofemoral compressive forces experienced during functional activities are believed to be important for maintaining tibiofemoral stability. Previous studies have shown that both knee-spanning and non-knee-spanning muscles contribute to tibiofemoral joint compressive forces during walking. However, healthy individuals typically engage in more vigorous activities (e.g. jumping and cutting) that provide greater challenges to tibiofemoral stability. Despite this, no previous studies have investigated how both knee-spanning and non-knee-spanning muscles contribute to tibiofemoral compressive loading during such tasks. The present study investigated how muscles contributed to the medial and lateral compartment tibiofemoral compressive forces during sidestep cutting. Three-dimensional marker trajectories, ground reaction forces and muscle electromyographic signals were collected from eight healthy males whilst they completed unanticipated sidestep cutting. OpenSim was used to perform musculoskeletal simulations to compute the contribution of each lower-limb muscle to compressive loading of each compartment of the knee. The greatest contributors to medial compartment loading were the vasti, gluteus maximus and medius, and the medial gastrocnemius. The greatest contributors to lateral compartment loading were the vasti, adductors, medial and lateral gastrocnemius, and the soleus. The soleus displayed the greatest potential for unloading the medial compartment, whereas the gluteus maximus and medius displayed the greatest potential for unloading the lateral compartment. These findings may help to inform interventions aiming to modulate compressive loading at the knee.